Gastric medullary carcinoma: Clinicopathological features and prognosis-a single-center study - AKMERCAN, AHMET; UPRAK, TEVFİK KIVILCIM (WILEY, 2021)
Background Gastric medullary carcinoma (GMC) is a distinct histologic subtype of gastric adenocarcinoma, which prominently associated with Epstein-Barr virus infection. This study aimed to evaluate the clinicopathological features and prognosis of patients with medullary carcinoma in one center. Methods Data regarding patients with gastric cancer were retrospectively analyzed at Marmara University between 2014 and 2019. Demographics, pathological features, and overall survival of patients with GMC were evaluated. The primary outcome of this study was to compare the pathological features of GMC to non-GMC (NGMC). The secondary outcome was comparing overall survival between the two groups. Results A total of 412 patients were enrolled in the study. Of 412 patients, 19 (5%) were diagnosed with medullary cancer. Compared to NGMC, no significant differences were observed in patient age, gender, tumor macroscopic pattern, size, lymphovascular invasion, pathological stage, location and size of the tumors, and the number of metastatic lymph nodes in GMC. However, perineural invasion and Borrmann ulcerated type rates were significantly higher among NGMC. Whereas the microsatellite instability (MSI) rate was significantly higher in the GMC (64% and 11%, respectively, p < 0.001). Multivariate analysis showed that the MSI status was the solely significantly different feature between the two groups. Conclusion This study showed that GMC was associated with MSI, which could explain the better prognosis of medullary carcinomas.
Keywords: gastric medullary carcinoma; microsatellite instability; stomach neoplasms; EPSTEIN-BARR-VIRUS; LYMPHOEPITHELIOMA-LIKE CARCINOMA; MICROSATELLITE INSTABILITY; LYMPHOID STROMA; CANCER